(untitled) (Progress Annals: Journal of Progressive Research, 2024)
The article presents experimental data on the study of the growth and development of Swiss bulls of various genotypes when raised for meat. It has been established that in order to further increase beef production, improve its quality and increase the profitability of the herd on farms, it is necessary to equip the herd with super-repair purebred and crossbred young animals of the Swiss breed.